2016
DOI: 10.1038/srep34439
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific sensitivity of bees towards dimethoate and implications for environmental risk assessment

Abstract: Wild and domesticated bee species are exposed to a variety of pesticides which may drive pollinator decline. Due to wild bee sensitivity data shortage, it is unclear if the honey bee Apis mellifera is a suitable surrogate species in the current EU risk assessment scheme. Furthermore, the underlying causes for sensitivity differences in bees are not established. We assessed the acute toxicity (median lethal dose, LD50) of dimethoate towards multiple bee species, generated a species sensitivity distribution and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 31 publications
(49 reference statements)
6
43
0
1
Order By: Relevance
“…It has been noted that the entire spectrum of bee species is not well represented because the honey bee is used as the only surrogate. Other bee species' sensitivity to pesticides is usually unknown (Arena and Sgolastra 2014;Uhl et al 2016). Because relative susceptibility varies for different pesticides, it is difficult to extrapolate acute toxicity data from the honey bee to wild bees (Biddinger et al 2013;Uhl et al 2016).…”
Section: Bee Risk Assessmentmentioning
confidence: 99%
“…It has been noted that the entire spectrum of bee species is not well represented because the honey bee is used as the only surrogate. Other bee species' sensitivity to pesticides is usually unknown (Arena and Sgolastra 2014;Uhl et al 2016). Because relative susceptibility varies for different pesticides, it is difficult to extrapolate acute toxicity data from the honey bee to wild bees (Biddinger et al 2013;Uhl et al 2016).…”
Section: Bee Risk Assessmentmentioning
confidence: 99%
“…However, there has been reasonable doubt that these two species are adequate to provide additional safety in lower tier risk assessment. Uhl et al (2016) tested five European bee species in acute contact exposure scenarios with a formulated insecticide product (PERFEKTHION ® ) containing dimethoate, which is often used as a toxic standard in regulatory testing [19]. They found that B. terrestris and O. bicornis were the least sensitive species when compared to a dataset of their own results and collected literature data.…”
Section: Introductionmentioning
confidence: 99%
“…In combination with the extensive experience and resulting robust test methodology makes A. mellifera solid choice as screening level test species. In contrast the relative sensitivity data indicates that the two recently developed model species Bombus terrestris and Osmia bicornis for the European risk assessment process are comparatively resilient to a range of insecticides, which in turn means that including them in the screening step will likely not make the risk assessment more protective for bees from a sensitivity perspective [12,13,66,67].…”
Section: Risk Assessment Considerationsmentioning
confidence: 96%